A handbook of environmental management - Lovett, Jon C.; Ockwell, David G.; Edward Elgar Publishing (Cheltenham, U.K. : Edward Elgar Pub. Ltd., 2010)
A Handbook of Environmental Management presents a range of case studies that demonstrate the complementary application of different social science techniques in combination with ecology-based management thinking to the natural environment. This eloquent and unique Handbook provides a broad overview, complemented by specific case studies and techniques that are used in environmental management from the local level to international environmental regimes.
1. Introduction / Jon C. Lovett and David G. Ockwell -- 2. Global biodiversity conservation priorities : an expanded review / Thomas M. Brooks ... [et al.] -- 3. Integrated conservation and development projects : a positive role for forest conservation in topical Africa? / Neil Burgess ... [et al.] -- 4. Biodiversity conservation in managed landscapes / Tom M. van Rensburg and Greig A. Mill -- 5. How do institutions affect the management of environmental resources? / Bhim Adhikari -- 6. Analysing dominant policy perspectives : the role of discourse analysis / David G. Ockwell and Yvonne Rydin -- 7. Theoretical perspectives on international environmental regime effectiveness : a case study of the Mediterranean action plan / Sofia Frantzi -- 8. The price of fish and the value of seagrass beds : socioeconomic aspects of the seagrass fishery on Quirimba Island, Mozambique / Fiona R. Gell -- 9. The link between ecological and social paradigms and the sustainability of environmental management : a case study of semi-arid Tanzania / Claire H. Quinn and David G. Ockwell -- 10. Exploring game theory as a tool for mapping strategic interactions in common pool resource scenarios / Vanessa Pérez-Cirera -- 11. Economic valuation of different forms of land-use in semi-arid Tanzania / Deborah Kirby -- 12. Economic growth and the environment / Dalia El-Demellawy -- 13. Biodiesel as the potential alternative vehicle fuel : European policy and global environmental concern / Mahesh Poudyal and Jon C. Lovett.
Includes bibliographical references and index.
Keywords: Environmental management; Electronic books